The Development of Indonesian Teaching Materials to Improve The Language Skills of Elementary School Students - Elfi Lailan Syamita Lubis (Pedagogik Journal of Islamic Elementary School, 2020)
This research is a type of research and development aimed at determining the feasibility and effectiveness of Indonesian language teaching materials to improve the language skills of elementary school students. The development of Indonesian teaching materials uses the ADDIE model development procedure. The development procedure used in this study includes 5 steps, namely: 1) Analysis; 2) Development or Production (Development); 3) Implementation or Delivery; (Application) 4) Evaluation (Assessment). The product developed is Indonesian language teaching materials to improve the language skills of elementary school students. The data collection instrument was in the form of an assessment sheet for material experts and Indonesian language teachers. The method used to analyze the data is descriptive qualitative which is expressed in the distribution of scores and categories of the rating scale. This development research produces Indonesian language teaching materials in the form of books, which meet the aspects of content, presentation, language and appearance with an average of 3.57 with a percentage of 71.3% in stage 1, namely in the good category, while in stage 2 the average score is 3. .9 with a percentage of 84.3% which is a very good category so it can be said that the criteria are valid and feasible to use. On the assessment sheet the Indonesian teacher got an average score of 4.28 in the very good category. For language skills, the listening aspect of elementary school students got an average score of 7.25%. In the aspect of speaking language skills, namely speaking based on pictures and getting an average score of 76% and the reading language skill aspect, the accuracy range is 80 and the essay writing skill aspect gets a score of 78%.